Peran Guru Dalam Pembelajaran Anak Hiperaktif di PAUD Aqilah Desa Bahung Sibatu-Batu Kec Sei Dadap Kab Asahan - Syahrizal Syahrizal; Aisyah Eka Suci (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
Every child has a different personality. So a teacher must be able to understand the character of the child, these differences make teachers complain about the behavior of school-age children today, they are confused about how to get students to sit quietly and follow the lesson so they can easily understand the material presented. This is one of the complaints of a teacher in dealing with hyperactive children. The role of TK, RA and PAUD educators as professionals is needed to help parents, especially those who are still cloudy in finding and obtaining information related to the causes of hyperactive children, the effects of hyperactive children and the handling of hyperactive children. This study aims to determine the teacher's role in the learning of hyperactive children in early childhood education in the village of Basung Sibatu-batu, Kec. Sei Dadap Kab. sharpen. The method used in this research is: qualitative research with a case study approach which is